Tari Kinyah Mandau Representasi Kerukunan Suku Dayak di Kalimantan Tengah - Aldia Wulandari; Tris Sofia Wartina; Tifan Muhammad Amirulloh (Universitas Negeri Medan, 2026)
In the past, Kalimantan Island was known as a difficult-to-access region, especially during the Asang period when headhunting and slavery were common due to conflicts between Dayak tribes. Attacks were generally carried out suddenly, but the Dayak people had a tradition of preparation through the Kinyah Mandau dance, which symbolized readiness, courage, and strength in facing enemies. The tense social conditions continued even during the Dutch colonial period, until finally the Resident of Banjarmasin initiated a large meeting that gave birth to the Tumbang Anoi Peace Conference (May 22–July 24, 1894). Since this historic event, the practice of violence has ceased and the Dayak tribes are committed to living in harmony. The Kinyah Mandau dance remains preserved, but its function has transformed from a war ritual to a cultural performance. In its new form, this dance is not merely entertainment, but a symbol of harmony and a medium for passing on noble values such as courage based on truth, responsible leadership, and social solidarity. Education plays a vital role in transmitting these values to the younger generation, ensuring that the Kinyah Mandau Dance not only survives as a cultural heritage but also becomes a representation of harmony and the collective identity of the Dayak people in Central Kalimantan.